Penegakan Hukum Atas Pencemaran Laut Akibat Kegiatan Pelayaran Kapal di Perairan Indonesia dari Perspektif Hukum Lingkungan - Damar Tangguh Rabani; Agnes Octavia Margaretha Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2024)
Marine pollution resulting from ship navigation activities is a primary concern in safeguarding the maritime environment in Indonesian waters. This article examines law enforcement regarding marine pollution from an environmental law perspective, focusing on existing regulations in Indonesia. Through a normative legal approach, the article identifies the legal framework governing the prevention and mitigation of marine pollution and the responsibilities of relevant parties. Additionally, employing a policy analysis approach, this article evaluates the effectiveness of implementing these regulations in addressing cases of marine pollution caused by ship navigation activities. The analysis reveals that while Indonesia possesses a relatively comprehensive legal framework, challenges persist in ensuring effective law enforcement, including inter-agency coordination and limited human resources. The article also offers recommendations for strengthening law enforcement and marine environmental protection in the future.